Evaluation of Student UX on E-Learning Web Using User Experience Questionnaire (UEQ) - Akhmad Nabil Darmawan; Asif Faroqi; Arista Pratama (bit-Tech, 2025)
User Experience (UX) in E-Learning systems plays a critical role in fostering student engagement and improving learning effectiveness. Evaluating UX is essential to address challenges such as reduced learning motivation, poor navigation, and low interface appeal, all of which can hinder educational outcomes. This study aims to evaluate the UX of students using the E-Learning system at SMP Muhammadiyah 17 Surabaya by employing the User Experience Questionnaire (UEQ), which measures six dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. A total of 180 students were selected using Slovin’s formula. Data were analyzed using the UEQ Data Analysis Tool (v10) through descriptive statistics and reliability testing (Cronbach’s alpha > 0.70). The results indicate that the dimensions of Attractiveness (M = 1.43), Efficiency (M = 1.35), Dependability (M = 1.43), and Stimulation (M = 1.34) received high scores and exceeded the average benchmark, indicating that the system is engaging, efficient, reliable, and motivating for users. The Perspicuity dimension (M = 1.42) was rated moderately high, though improvements are needed to better support the understanding of complex materials. In contrast, the Novelty dimension (M = 0.28) scored low, suggesting a lack of innovation and freshness in the interface. These findings highlight the pedagogical significance of UX in enhancing student engagement and online learning effectiveness. Developing more innovative features such as gamified elements or adaptive feedback is recommended to increase the appeal and sustained use of the E-Learning system in alignment with educational goals.